2000
DOI: 10.1021/np000029g
|View full text |Cite
|
Sign up to set email alerts
|

Activity of Extracts and Isolated Naphthoquinones from Kigelia pinnata against Plasmodium falciparum

Abstract: Four naphthoquinoids from Kigelia pinnata rootbark were assessed in vitro against chloroquine-sensitive (T9-96) and -resistant (K1) Plasmodium falciparum strains and for cytotoxicity using KB cells. 2-(1-Hydroxyethyl)naphtho[2,3-b]furan-4,9-dione possessed good activity against both strains [IC(50) values 627 nM (K1), 718 nM (T9-96)]. Isopinnatal, kigelinol, and isokigelinol exhibited lower activity against both strains.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
38
0

Year Published

2002
2002
2022
2022

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(39 citation statements)
references
References 25 publications
0
38
0
Order By: Relevance
“…Quinones have been tested intensively in the past against different parasites including Plasmodium (Weiss et al 2000;Bezabih et al 2001), Leishmania (Kayser et al 2000;Teixeira et al 2001), Toxoplasma gondii (Khan et al, 1998) and Trypanosoma sp. (Lopes et al 1978;Pinto et al 2000).…”
Section: Naphthoquinones and Related Quinonesmentioning
confidence: 99%
“…Quinones have been tested intensively in the past against different parasites including Plasmodium (Weiss et al 2000;Bezabih et al 2001), Leishmania (Kayser et al 2000;Teixeira et al 2001), Toxoplasma gondii (Khan et al, 1998) and Trypanosoma sp. (Lopes et al 1978;Pinto et al 2000).…”
Section: Naphthoquinones and Related Quinonesmentioning
confidence: 99%
“…Nevertheless, in general the anticancer and antiprotozoal activities have been attributed to the quinone compounds, especially the furanonaphtoquinoids characteristic for this species e.g. isopinnatal, kigelinole and isokigelinol, and kigelinone [22,23,27,43], the latter being characterized as cytotoxic agent and identified in other plants used as traditional antineoplastic remedies [16,44]. Moreover, quinone structural fragment is found in some important anticancer drugs, or investigational cytotoxic agents including the anthracycline antibiotics, mitoxanthrone, aloeemodin, lapachol (an identified constituent of K. africana) [21,35,[45][46][47][48] etc.…”
Section: Discussionmentioning
confidence: 99%
“…This research interest is related to the traditional uses of bark and fruit extracts throughout Africa as remedies for treating sexually transmitted diseases, dysentery, leprosy, miscellaneous microbial and parasitic infections, skin ulcers, and neoplastic diseases [13,14,16,26]. Moreover, extracts from the plant, as well as isolated compounds, have been found to exert a constellation of other pharmacological effects, including antifungal [24], antiprotozoal (against Trypanosoma brucei brucei, Trypanosoma brucei rhodesiense [23], and several, including multi-drug resistant, strains of Plasmodium falciparum [27][28][29]), antiinflammatory and analgesic [15,19], hepatoprotective [30], anti-fertility [31], CNS-stimulant, antidiarrheal, and antidiabetic [13,14,32], among others.…”
mentioning
confidence: 99%
“…Other naphthoquinones act by inducing oxidative stress, reducing the consumption of oxygen in the respiratory chain, and inhibiting electron transport (Colman de Saizarbitoria et al 1997). It has also been reported that the activity of naphthoquinones against sensitive and resistant strains of Plasmodium falciparum to chloroquine may be due to the presence of a methyl group which increases its lipophilicity promoting drug accumulation in the mitochondria of the parasite (Weiss et al 2000). Naphthoquinones 2 and 3 exhibited significant activity against tumor cells KB (Rao and Kingston 1982;Zani et al 1991).…”
Section: Identification and Effects Of Mixtures And Isolated Compoundsmentioning
confidence: 98%
“…Naphthoquinones 2 and 3 exhibited significant activity against tumor cells KB (Rao and Kingston 1982;Zani et al 1991). In addition, naphthoquinone 3 showed significant activity against Trypanosoma brucei brucei, Trypanosoma brucei rhodesiense, P. falciparum, and P. berghei (Weiss et al 2000;Fournet and Muñoz 2002) and against a wide range of microorganisms (Kuete et al 2007). Naphthoquinone 3 could have an antiparasitic mode of action similar to that described for other naphtoquinones, while the presence of a hydroxyethyl group in its side chain could be responsible for an increase in activity compared to 2.…”
Section: Identification and Effects Of Mixtures And Isolated Compoundsmentioning
confidence: 99%